PERBEDAAN RISK AND RETURN DEPOSITO MUDHARABAH PADA BUS DI INDONESIA (PERIODE 2015-2017) - Noer Cholilah; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research analyzes the level of potential risks and returns received by customers from mudharabah deposit investments. In this study the authors also analyzed the relationship between the two variables whether they have differences in.The research method used is a descriptive quantitative approach. The sample in this study were 9 Islamic Commercial Banks which included: Bank Syariah Mandiri, Bank Muamalat Indonesia, BRI Syariah, BNI Syariah, BCA Syariah, Panin Syariah Bank, Syariah BTPN Bank, Maybank Syariah Indonesia, and Bank Syariah Bukopin. The results of this study indicate that there are significant differences between the risks with investment in mudharabah deposits in Islamic Commercial Banks. The support of this hypothesis is based on the average value of Risk on mudharabah deposit investment in Islamic Commercial Banks of -0.06448, and a significance value of 0.038 (p <0.05). This shows that the two variances are not the same and different.Keywords: Risk, Yield, futures investment, mudharabah depositsREFFERENCESAl Qur’an dan Terjemahannya. 2014. Jakarta: Kementrian Agama RI.Anshori, Muslich Dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kualitatif. Surabaya: Pusat Penerbitan dan Percetakan Unair (AUP).Ascaraya.2008. Akad dan Produk Bank Syariah. Jakarta: PT Raja Grafindo Persada.Aziz, Abdul. 2010. Manajemen Investasi Syariah. Bandung: Alfabeta.Basyaib Fachmi. 2007. Manajemen Risiko. Jakarta: PT Gramedia.Fahmi, Irham. 2013. Rahasia Saham dan Obligasi. Bandung: Alfabeta.___________. 2015. Manajemen Investasi: Teori dan Soal Jawab, Edisi 2. Jakarta Selatan: Salemba Empat.Halim, Abdul. 2009. Analisis Kelayakan Investasi Bisnis Kajian dari Aspek Keuangan, Edisi pertama. Yogyakarta: Graha IlmuHasibuan, Melayu S.P. 2001. Dasar-Dasar Perbankan. Jakarta: PT Bumi Aksara.Hidayat, Taufik. 2011. Buku Pintar Investasi Syariah. Jakarta : Media Kita.Huda, Nurul. 2008. Investasi Pasar Modal Syariah, Edisi Revisi. Jakarta: Kencana.Hull, J.. 2007. Risk Management And Financial Institutions. 2nd ed. Boston: Pearson.Ismail. 2011. Perbankan Syariah. Jakarta: Kencana.Idrus, N Ferry. 2011. Manajemen Risiko Perbankan Syariah. Jakarta: PT Raja Grafindo Persada.Jogiyanto.2000. Teori Portofolio dan Analisis Investasi, Edisi Kelima. Yogyakarta: PT BPFE Yogyakarta.Jorion, P.H.. 1996. Value at Risk: The New Brenchmark for Measuring Derivatives Risk, third ed. McGraw-Hill, New York, NY.Karim, Adiwarman. 2010. Bank Islam: Analisis Fiqih dan Keuangan, Edisi 4. Jakarta: PT Raja Grafindo Persada. Kasmir. 2008. Analisis Laporan Keuangan. Jakarta: PT Raja Grafindo Persada.______. 2008. Bank dan Lembaga Keuangan, Edisi Revisi. Jakarta: PT Raja Grafindo Persada.______. 2010. Manajemen Perbankan. Jakarta: Rajawali Pers.Khairunnisa, Anindytia Clara. 2015. Risk Adjusted Return On Capital dan Economic Value Added Studi Empiris pada Industri Perbankan pada Tahun 2008-2013. Volume 2.Markowitz, H. 1952. Portofolio Selection.Jurnal of Finance 7: pp77-91.Muhammad. 2005. Manajemen Bank Syariah: Edisi Revisi, Cet. 1 . Yogyakarta: UPP AMP YKPN. Peraturan Bank Indonesia No.5/8/PBI/2003; diakses pada tanggal 28 Desember 2018 pukul 18.25 wib dari http://www.bi.go.id/Sudarsono, Heri. 2008. Bank dan Lembaga Keuangan Syariah, Cetakan Ke-2. Yogyakarta: Ekonisia.Sunariyah. 2004. Pengantar Pengetahuan Pasar Modal: Edisi Kelima. Bandung: CV Alfabeta.Tambunan. 2007. Menilai Harga Wajar Saham. Jakarta: PT Gramedia Pusaka Utama.Tandelilin Eduardus. 2011. Analisis Investasi dan Manajemen Portofolio: Edisi Pertama. Yogyakarta: Ekonisia.Wiroso.2011. Produk Perbankaan Syariah, Cetakan Ke-2. Jakarta: LPFE Usakti.Wiku Suryomurti. Konsep dalam Islam, artikel diakses pada tanggal 28 Desember 2018 pukul 18.50 wib dari http://www.wikusuryomurti.com/konsep-dalam-Islam/Yudho, Prabowo. 2009. Analisis Resiko dan Pengembalian Hasil pada Perbankan Syariah: Aplikasi Metode VaR dan RAROC pada BSM. Jurnal Ekonomi Islam La_Riba Vol. III. No.1.Yogyakarta: Fakultas Ilmu Agama Islam UII.